Unusual twinning: Additional findings during prenatal diagnosis of twin zygosity by single nucleotide polymorphism (SNP) array. (15th April 2018) - Zou, Zhiyong; Huang, Linhuan; Lin, Shaobin; He, Zhiming; Luo, Yanmin
Abstract: Objective: To evaluate the incidence and characteristics of unusual twinning by using single nucleotide polymorphism (SNP) array to identify twin zygosity. Methods: This study reviewed 386 twin pairs who were seen for prenatal or postnatal diagnosis and underwent SNP array to detect zygosity. Results: The incidence of monozygotic (MZ) twins was 11.36% (25/220) in the assisted reproductive technology (ART)‐conceived group. Monochorionic dizygotic twins represented 3 of 24 monochorionic ART‐conceived twin pairs (3/24, 12.50%) but none in the spontaneous twin pairs. Among 4 single‐embryo transfer twin pairs, 3 represented unusual twinning, including 2 MZ twin pairs with discordant karyotypes and 1 dizygotic twin pair of the same gender. Of the pregnancies with 2 or more embryos transferred, 7.77% (15/193) were MZ. Additionally, there was a dichorionic monozygotic twin pair with placental vascular anastomoses from a day‐5 blastocyst transfer. Conclusion: Single nucleotide polymorphism array can provide zygosity diagnosis in addition to chromosomal copy number variation and uniparental disomy detection. ART twin pregnancies have a risk of unusual twinning, such as monochorionic dizygotic, single‐embryo transfer twin pairs with discordant karyotypes or dizygotic, and dichorionic monozygotic with vascular anastomoses from day‐5 transfer. Abstract : WHAT'S ALREADY KNOWN ABOUT THIS TOPIC? SNP array is a valuable tool for evaluating fetal chromosomal copy number variations (CNVs) and uniparental disomy (UPD) via invasive diagnosis. Zygosity may be judged by chorionicity, sex, and number of embryos transferred. WHAT DOES THIS STUDY ADD? SNP array can provide zygosity diagnosis. Twin pregnancies conceived by assisted reproductive technology (ART) have a risk of unusual twinning, and zygosity determination is essential in the management of these twin pregnancies.